2020
DOI: 10.1177/0312896220922292
|View full text |Cite
|
Sign up to set email alerts
|

A review and agenda for examining how technology-driven changes at work will impact workplace mental health and employee well-being

Abstract: The mental health and well-being of employees is an increasingly important issue, both in terms of the financial costs to the Australian economy and human costs to society. This review examines two major technology-driven trends in the workplace and presents evidence for their impact on mental health, both positive and negative. First, we consider how we work, with a focus on changes which have been driven by automation and advanced technology in the workplace. Next, we consider where and when we work, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 102 publications
(121 reference statements)
1
63
0
Order By: Relevance
“…It has benefits, as well as disadvantages, for workers (Hamouche, 2020). In terms of benefits, Johnson et al (2020) point out that the flexibility associated with remote work would facilitate the planning and adjustment of working hours for family tasks, which would improve worker control and autonomy, while preventing anxiety and depression during abrupt transitions. Baert et al (2020) add that remote work during COVID-19 has generally increased job satisfaction and efficiency, concentration, and work-life balance, while reducing workrelated stress and the risk of burnout.…”
Section: The Effects Of Remote Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It has benefits, as well as disadvantages, for workers (Hamouche, 2020). In terms of benefits, Johnson et al (2020) point out that the flexibility associated with remote work would facilitate the planning and adjustment of working hours for family tasks, which would improve worker control and autonomy, while preventing anxiety and depression during abrupt transitions. Baert et al (2020) add that remote work during COVID-19 has generally increased job satisfaction and efficiency, concentration, and work-life balance, while reducing workrelated stress and the risk of burnout.…”
Section: The Effects Of Remote Workmentioning
confidence: 99%
“…Baert et al (2020) add that remote work during COVID-19 has generally increased job satisfaction and efficiency, concentration, and work-life balance, while reducing workrelated stress and the risk of burnout. Nevertheless, there are disadvantages to remote work, such as social isolation and loneliness, particularly related to the decrease in interactions between colleagues, and an increase in family conflicts, particularly concerning work-family balance (Johnson et al 2020). In the same vein, in her literature review about remote work during COVID-19, Hamouche (2020) identified difficulties in demarcating borders between private and professional life, therefore increasing workloads (e.g., hours spent working).…”
Section: The Effects Of Remote Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For remote e-workers, communication with colleagues and supervisors plays a critical role in psychological well-being by sharing information and work processes, identifying problems and implementing solutions, and building relationships in work groups (Crawford et al, 2011;Nayani et al, 2018). When remote e-workers have more opportunities to develop and maintain social relationships with colleagues and managers, they have higher levels of psychological well-being because they are less likely to feel excluded from the workplace (Johnson et al, 2020). Support from colleagues and supervisors can help remote e-workers perceive psychological well-being by allowing them to seek advice from co-workers and managers and to link to work groups (Nayani et al, 2018).…”
Section: Factors Supporting Remote E-workers' Psychological Well-beingmentioning
confidence: 99%
“…In the modern era, work-related stress has been greatly exacerbated by adversarial psychosocial working conditions. It is the organizations' responsibility to look after the mental health and well-being of employees (Johnson et al, 2020). It is imperative that the 'third goal' of Sustainable Development Goals (SDGs) of the United Nations is to focus on "good health and wellbeing," which has increased awareness and importance among policymakers and researchers globally (George et al, 2016).…”
Section: Introductionmentioning
confidence: 99%